The Suzuki method precedes a philosophy (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
The aim of this article is to present a scenic and historical context that precedes and follows the beginning of the career of Japanese director Tadashi Suzuki, as well as synthetically exposing technical and theoretical principles that define his notion of staging. Starting from his biography, from childhood in the post-World War II context to his early years as a professional director, we seek to expose the combination of aspects of Eastern and Western theaters that led to the development of the Suzuki method. Finally, based on the director's own writings, we intend to summarize his technical and theoretical vision of acting.
Keywords: Contemporary Japanese theater; Suzuki method; Training for actors; Tadashi Suzuki; SCOT Company